Method for preparing special-shaped porous material through additive manufacturing technology
Through direct writing 3D printing technology, water is used as a curing agent to prepare a special-shaped porous material with a three-level macroporous structure, which solves the problem that traditional processes cannot prepare complex porous structures and micro-size porous materials, and realizes special-shaped porous materials Effective application in various application fields.
Patent Information
- Application Number
- CN202411780914.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional porous material preparation processes cannot prepare complex pore structures and micro-size porous materials, and cannot prepare special-shaped devices, limiting the development of porous materials in the application of special-shaped devices.
Using a direct-write 3D printing process with water as a curing agent, polyether sulfone, polyvinylpyrrolidone and N,N-dimethylpyrrolidone are mixed and dissolved, forming a phase conversion solution and mixing it with powder material, and preparing a Porous materials of three-level macroporous structures.
Special-shaped porous ceramics, carbon materials and carbon nitride materials with corresponding porosity were successfully prepared, which are suitable for solid oxide fuel cell anode support tubes, thermal energy storage carrier materials porous carbon materials and lithium sulfur battery anode support porous silicon carbide materials.
Smart Images

Figure CN119462082A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing special-shaped porous materials, and relates to a method for preparing special-shaped porous materials by using additive manufacturing technology. Background Art
[0002] Porous materials occupy an important position in the field of functional materials, mainly including porous ceramics, porous organic materials, porous carbon materials, porous metals, etc. Due to their good chemical stability, certain mechanical strength, low thermal conductivity, high temperature resistance, and large specific surface area, porous materials have unique properties and advantages in the fields of lightweight heat-resistant materials, thermal insulation materials, absorbing materials, energy storage devices, highly sensitive sensors and catalyst carriers.
[0003] Traditional methods for preparing porous materials mainly include sol-gel method, extrusion molding, foaming method, sacrificial template method and freeze-drying method. Due to its atomic-level reaction, the sol-gel method produces uniform pores in the product, but it requires that the raw materials must be able to undergo hydrolysis reaction, which limits the types of porous materials; the extrusion molding method has a simple preparation process, and the pore distribution and size of the material can be adjusted by adjusting the extrusion parameters of the equipment, but it cannot prepare complex pore structures and micro-sized porous materials; the freeze-drying method has a simple process, but a long preparation cycle; the sacrificial template method uses small organic molecules or polymers as templates to grow highly ordered pore structures through self-assembly, but the template removal process is more complicated and brings higher costs. In addition, traditional preparation processes are all subtractive manufacturing, and macroscopic special-shaped devices cannot be prepared, which limits the application of porous materials in the preparation of special-shaped devices.
[0004] 3D printing, or additive manufacturing, has gradually become one of the mainstream processes for building multi-level porous structure materials in recent years due to its ability to achieve complex geometric shapes and precise control of the internal structure of devices. According to different mechanical principles and molding principles, 3D printing technology mainly includes direct writing 3D printing, laser melting, fused deposition, selective laser sintering, inkjet printing, photocuring and other printing systems based on the principle of photocuring.
[0005] Among them, direct writing 3D printing has a relative advantage in the preparation of devices with low precision requirements due to its simple process and low cost. Researchers generally use thermal curing, photocuring, etc. as the curing means of direct writing 3D printing sample embryos, and control the porosity and pore structure by controlling the amount of pore-forming agent and the post-sintering process. The non-solvent induced phase separation method is generally used for film preparation. It takes advantage of the stronger miscibility of non-solvents and solvents, adds them to the polymer homogeneous solution, and makes the polymer precipitate to achieve phase inversion. This principle is applied to the curing process of 3D printing, which simplifies the curing process of the slurry and reduces the reaction cost. At the same time, due to the precipitation mechanism under different precipitation conditions, the pore structure can be further controlled. Summary of the invention
[0006] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0007] The present invention uses water as a curing agent to prepare special-shaped porous ceramics, special-shaped porous carbon materials and special-shaped porous carbon nitride materials through a direct writing 3D printing process, and explores a new preparation process suitable for special-shaped porous materials such as ceramic materials and carbon materials.
[0008] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a special-shaped porous material by additive manufacturing technology is provided, comprising the following steps:
[0009] Step 1: Mix and dissolve polyethersulfone (PESF), polyvinylpyrrolidone (PVP, K30) and N,N-dimethylpyrrolidone (NMP) to obtain a phase conversion solution;
[0010] Step 2: Evenly mix the phase conversion solution and the powder material to obtain a viscous slurry;
[0011] Step 3: Set the 3D printing model as needed, inject the viscous slurry into the direct writing 3D printer, adjust the printing parameters, print the model, and obtain a sample green body with a three-level macroporous structure;
[0012] Step 4: transferring the green sample into deionized water for curing;
[0013] Step 5: vacuum dry the solidified sample and then sinter it to obtain a special-shaped porous material.
[0014] Preferably, in the step 1, the mass ratio of polyethersulfone, polyvinylpyrrolidone and N,N-dimethylpyrrolidone is 2-5:1:7-20.
[0015] Preferably, in the step 2, the mass ratio of the powder material to the phase conversion solution is 5-15:2-13; and the phase conversion solution and the powder material are mixed uniformly by grinding and mixing.
[0016] Preferably, in the step 2, the powder material is a mixed powder material obtained by ball milling NiO, 8YSZ and graphite for 12 to 36 hours; wherein NiO and 8YSZ are mixed in a mass ratio of 65wt%:35wt%, and then 5 to 12.5wt% of graphite is added; and in the step 5, the sintering process is: the sample is heated to 1000 to 1100°C at a heating rate of 1 to 3°C / min in an air atmosphere in a tubular furnace and kept warm for 3 to 6 hours, then heated to 1350 to 1450°C at a heating rate of 1 to 3°C / min and kept warm for 3 to 6 hours, the temperature in the furnace is naturally reduced, and then placed in a tubular furnace and heated to 750 to 850°C at a heating rate of 1 to 3°C / min in a hydrogen atmosphere, and kept warm for 1 to 3 hours.
[0017] Preferably, in step 2, the powder material is a mixture of single-layer graphene oxide and carboxylated multi-walled carbon nanotubes; and in step 5, the sintering process is: heating the sample to 950-1100° C. in an Ar gas atmosphere using a tubular heating furnace, keeping the temperature for a period of time, and then cooling.
[0018] Preferably, in step 2, the powder material is SiC; and in step 5, the sintering process is: heating the sample to 950-1100° C. in an Ar gas atmosphere using a tubular heating furnace, keeping the temperature for a period of time, and then cooling.
[0019] Preferably, in the step three, the printing parameters are: extruding the slurry at a pressure of 0.1-0.6 MPa, a moving speed of 0.5-5 mm / s, and a nozzle diameter of 0.2-1 mm; in the step four, the curing time is 6-18 hours; in the step five, the vacuum drying temperature is 80-100°C.
[0020] The present invention also provides an application of the special-shaped porous material prepared by the preparation method as described above in an anode support tube of a solid oxide fuel cell.
[0021] The present invention also provides an application of the special-shaped porous material prepared by the preparation method as described above in porous carbon materials as thermal energy storage carrier materials.
[0022] The present invention also provides an application of the special-shaped porous material prepared by the preparation method as described above in a porous silicon carbide material as an anode carrier of a lithium-sulfur battery.
[0023] The present invention has at least the following beneficial effects:
[0024] (1) The present invention has successfully prepared a solid oxide fuel cell anode support with corresponding porosity and a tertiary pore structure, a porous carbon material as a thermal energy storage carrier material, and a porous silicon carbide material as a lithium-sulfur battery anode carrier according to the model design by testing the slurry performance during the device preparation process and characterizing the device pore structure.
[0025] (2) The special-shaped porous material prepared by the present invention has a high porosity and can be better applied in the anode support tube of solid oxide fuel cells, porous carbon materials as thermal energy storage carrier materials, and porous silicon carbide as anode carriers of lithium-sulfur batteries.
[0026] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the rheological properties of the slurry of Example 1;
[0028] Figure 2 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 1;
[0029] Figure 3 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 2;
[0030] Figure 4 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 3;
[0031] Figure 5 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 4;
[0032] Figure 6 This is a pore size distribution diagram of the solid oxide fuel cell anode support tube prepared in Example 1;
[0033] Figure 7 This is a pore size distribution diagram of anode support tube of a solid oxide fuel cell prepared in Example 2;
[0034] Figure 8 This is a pore size distribution diagram of anode support tube of a solid oxide fuel cell prepared in Example 3;
[0035] Fig. 9 This is a pore size distribution diagram of anode support tube of a solid oxide fuel cell prepared in Example 4;
[0036] Fig.10 is the rheological properties of the slurry of Example 5;
[0037] Fig.11 (a) is a SEM image of the surface of the porous carbon material, a thermal energy storage carrier material, prepared in Example 5;
[0038] Fig.11 (b) is a SEM image of a cross section of a porous carbon material as a thermal energy storage carrier material prepared in Example 5;
[0039] Fig.12 The pore size distribution diagram of the porous carbon material which is a thermal energy storage carrier material prepared in Example 5;
[0040] Fig.13 is the rheological properties of the 3D printing slurry in Example 6;
[0041] Fig.14 (a) is a SEM image of the surface of the porous silicon carbide material of the lithium-sulfur battery anode carrier prepared in Example 6;
[0042] Fig.14 (b) is a SEM image of the cross section of the porous silicon carbide material for the lithium-sulfur battery anode carrier prepared in Example 6;
[0043] Fig.15 This is the pore size distribution diagram of the porous silicon carbide material as the lithium-sulfur battery anode carrier prepared in Example 6.
[0044] Fig.16 (a) is a SEM image of a cross section of a single cell of a tubular solid oxide fuel cell of Application Example 1;
[0045] Fig.16 (b) is a SEM image of the anode support layer of a single cell of a tubular solid oxide fuel cell of Application Example 1;
[0046] Fig.16 (c) is a SEM image of the electrolyte layer and cathode layer of a single cell of a tubular solid oxide fuel cell of Application Example 1;
[0047] Fig.16 (d) is a SEM image of the cathode of a single cell of a tubular solid oxide fuel cell of Application Example 1;
[0048] Fig.17 The cell impedance performance of a single cell of a tubular solid oxide fuel cell of Application Example 1;
[0049] Fig.18 The cell electrochemical performance of the tubular solid oxide fuel cell cell of Application Example 1. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0051] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.
[0052] Embodiment 1:
[0053] A method for preparing a special-shaped porous material by additive manufacturing technology comprises the following steps:
[0054] (1) Slurry preparation: NiO and 8YSZ powders were mixed in a mass ratio of 65wt%:35wt%, and 5wt% of graphite was added (5wt% content is relative to the total amount of NiO and 8YSZ powders), and ball milled for 24h to obtain anode powder; a phase conversion solution was prepared in a mass ratio of NMP:PESF:PVP(K30)=20:5:1; the anode powder and the phase conversion solution were evenly ground in a mass ratio of 12:5 to obtain 3D printing slurry;
[0055] (2) Direct writing 3D printing was performed according to the designed 3D printing model: the slurry was extruded at a pressure of 0.2 MPa using a direct writing 3D printer, with a moving speed of 0.8 mm / s and a nozzle diameter of 0.58 mm; the models were support tubes with a wall thickness of 0.58 mm, a tube diameter of 7.5 mm, and a height of 28 mm; after the model was printed, the sample was quickly transferred to deionized water and soaked for 12 h for curing;
[0056] (3) Post-treatment: The solidified samples were dried in a vacuum drying oven at 80-100°C. To simulate the entire preparation process of the solid oxide anode supported tubular battery, the samples were heated to 1050°C at a rate of 3°C / min in an air atmosphere in a tubular furnace and kept at that temperature for 5 h. The temperature was then raised to 1400°C at a rate of 1°C / min and kept at that temperature for 5 h. The temperature was naturally lowered in the furnace. The samples were then placed in a tubular furnace and heated to 800°C at a rate of 3°C / min in a hydrogen atmosphere and kept at that temperature for 3 h to reduce NiO to Ni, thereby obtaining a special-shaped porous material, namely, a solid oxide fuel cell anode support tube.
[0057] Embodiment 2:
[0058] Compared with Example 1, 7.5 wt% of graphite is added in step (1), and the rest is the same as that of Example 1.
[0059] Embodiment 3:
[0060] Compared with Example 1, 10.5 wt% of graphite is added in step (1), and the rest is the same as that of Example 1.
[0061] Embodiment 4:
[0062] Compared with Example 1, 12.5 wt% of graphite is added in step (1), and the rest is the same as that of Example 1.
[0063] The slurry fluidity of Example 1 above is characterized as follows:
[0064] Figure 1The rheological properties of the slurry in Example 1 are as follows: according to the rheological test results, the slurry is a non-Newtonian body with shear thinning properties, that is, the slurry can be squeezed out of the nozzle under a certain pressure; when the angular frequency is 1.25-2.5 rad / s, the storage modulus is equivalent to the loss energy, indicating that the slurry is in a semi-solid state, after 2.5 rad / s, the storage modulus exceeds the loss modulus, the slurry mainly undergoes elastic deformation, the formability is enhanced, and the slurry can maintain a stable shape after extrusion.
[0065] The cross-section of the solid oxide fuel cell anode support tube prepared in the above-mentioned embodiments 1 to 4 was characterized by SEM;
[0066] Figure 2 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 1; it can be seen from the figure that this example obtains an anode support layer with uniform distribution of Ni and 8YSZ grains and a certain porosity;
[0067] Figure 3 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 2; it can be seen from the image that this example obtains an anode support layer with uniform distribution of Ni and 8YSZ grains and a certain porosity;
[0068] Figure 4 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 3; it can be seen from the image that this example obtains an anode support layer with uniform distribution of Ni and 8YSZ grains and a certain porosity;
[0069] Figure 5 This is a SEM image of the solid oxide fuel cell anode support tube prepared in Example 4; it can be seen from the image that this example obtains an anode support layer with uniform distribution of Ni and 8YSZ grains and a certain porosity;
[0070] The pore size distribution analysis was performed on the cross section of the solid oxide fuel cell anode support tube prepared in Examples 1 to 4 above;
[0071] Figure 6 This is a pore size distribution diagram of the solid oxide fuel cell anode support tube prepared in Example 1; the porosity of the solid oxide fuel cell anode support tube prepared in this example is 30.6728%;
[0072] Figure 7 This is a pore size distribution diagram of the solid oxide fuel cell anode support tube prepared in Example 2; the porosity of the solid oxide fuel cell anode support tube prepared in this example is 32.8121%;
[0073] Figure 8This is a pore size distribution diagram of the solid oxide fuel cell anode support tube prepared in Example 3; the porosity of the solid oxide fuel cell anode support tube prepared in this example is 33.1312%;
[0074] Fig. 9 This is a pore size distribution diagram of the solid oxide fuel cell anode support tube prepared in Example 4; the porosity of the solid oxide fuel cell anode support tube prepared in this example is 38.1999%;
[0075] Application Example 1:
[0076] On the solid oxide fuel cell anode support tube prepared in Example 1, an anode functional layer, an electrolyte layer, a barrier layer and a cathode are prepared respectively by dip-coating, brush coating and post-sintering treatment to obtain a tubular solid oxide fuel cell single cell; that is, a single cell with a battery system of Ni-8YSZ / Ni-8YSZ / 8YSZ / GDC / LSCF-GDC is prepared with an anode support layer having a pore-forming agent content of 5%, and a nozzle diameter of 0.58 mm;
[0077] Fig.16 (a) shows that the battery thickness is 0.64mm, Fig.16 (b) shows the uniform pore structure of the anode support layer and the well-dispersed Ni and YSZ. Fig.16 (c) shows that the thickness of the electrolyte layer is about 14 μm and the cathode layer is about 24 μm; Fig.16 (d) is a loose and porous cathode structure;
[0078] When conducting electrochemical tests on a single cell, moist hydrogen was introduced into the anode as fuel at 800°C, and the cathode was placed in a static air atmosphere. Fig.17 The battery impedance performance is 0.80Ωcm 2 , polarization impedance is 1.21Ωcm2, Fig.18 The electrochemical performance of the battery is as follows: the open circuit voltage is 0.979V and the power density is 136mW / cm 2 .
[0079] Embodiment 5:
[0080] A method for preparing a special-shaped porous material by additive manufacturing technology comprises the following steps:
[0081] (1) Preparation of slurry: monolayer graphene oxide and carboxylated multi-walled carbon nanotubes in a mass ratio of 2:1 were stirred evenly, a thickener (NMP:PESF:PVP=7:2:1) was added (the mass ratio of the total mass of monolayer graphene oxide and carboxylated multi-walled carbon nanotubes to the thickener was 1:7), and the mixture was ground in a mortar to obtain a viscous slurry with a certain fluidity;
[0082] (2) Direct writing 3D printing was performed according to the designed 3D printing model: a 3D direct writing printer was used to print at a pressure of 0.4 MPa, a spraying speed of 2 mm / s and a moving speed of 5 mm / s. After printing, a certain amount of deionized water was injected into it, and then it was immersed in deionized water for 12 hours;
[0083] (3) Post-processing: The printed samples were vacuum dried in a vacuum drying oven at 100°C, and then kept at 1000°C for 3 h in a tubular heating furnace and then cooled (Ar gas) to obtain a special-shaped porous material, i.e., a porous carbon material as a thermal energy storage carrier material.
[0084] Fig.10 is the rheological property of the slurry of Example 5, Fig.10 It can be seen that as the angular frequency gradually increases, the viscosity of the slurry gradually decreases, and it is a non-Newtonian fluid with shear thinning properties, that is, the slurry can be squeezed out of the nozzle under a certain pressure; the storage modulus and shear modulus of the slurry gradually increase with the increase of the angular frequency. At a smaller angular frequency (<1.5rad / s), the storage modulus is equivalent to the loss modulus, indicating that the slurry is in a semi-solid state at this time. After being greater than 1.5rad / s, the storage modulus is less than the loss modulus, that is, the slurry mainly undergoes viscous deformation, and the fluidity is enhanced. After the slurry is extruded, the adhesion between layers is better, thereby improving the printing quality.
[0085] Fig.11 (a) and Fig.11 (b) is a SEM image of the porous carbon material as a thermal energy storage carrier material prepared in Example 5. As can be seen from the image, the porous carbon material has a rich pore structure.
[0086] The pore size distribution of porous carbon materials used as thermal energy storage carriers was analyzed by fully automatic mercury intrusion porosimetry. Fig.12 As shown, the total porosity of the porous carbon material reaches 75.36%, which proves the high porosity of the porous material.
[0087] Embodiment 6:
[0088] A method for preparing a special-shaped porous material by additive manufacturing technology comprises the following steps:
[0089] (1) Slurry preparation: SiC and thickener (NMP:PESF:PVP=20:5:1) were ground evenly according to a mass ratio of 10:11 to obtain 3D printing slurry;
[0090] (2) Direct writing 3D printing is performed according to the designed 3D printing model: the slurry is extruded by a direct writing 3D printer at a pressure of 0.2 MPa, a moving speed of 1-3 mm / s, and a nozzle diameter of 0.25 mm; after the model printing is completed, the sample is quickly transferred to deionized water and soaked for 12 hours for curing;
[0091] (3) Post-treatment: The cured sample was dried in a vacuum drying oven at 100°C, and then placed in a tubular furnace, and Ar gas was introduced at a heating rate of 1°C / min. The temperature was first raised from room temperature to 200°C, and then kept at 200°C for two hours. The temperature was then raised to 400°C and kept at this temperature for two hours. The temperature was then raised to 800°C and kept at this temperature for two hours. Finally, the temperature was raised to 1000°C, and after keeping at this temperature for two hours, the sample was naturally cooled to room temperature to obtain a special-shaped porous material, i.e., a porous silicon carbide material for anode carrier of a lithium-sulfur battery.
[0092] Fig.13 The rheological properties of the 3D printing slurry in Example 6 are as follows: according to the rheological test results, the slurry is a non-Newtonian fluid with shear thinning properties, that is, the slurry can be squeezed out of the nozzle under a certain pressure; when the angular frequency is 1.9-3.15 rad / s, the storage modulus is equivalent to the loss energy, indicating that the slurry is in a semi-solid state, after 3.15 rad / s, the loss modulus exceeds the storage modulus, the slurry mainly undergoes viscous deformation, and the fluidity is enhanced. After the slurry is extruded, the adhesion between the layers is better, thereby improving the printing quality.
[0093] Fig.14 (a) and Fig.14 (b) is a SEM image of the porous silicon carbide material of the lithium-sulfur battery anode carrier prepared in Example 6. It can be seen from the figure that the silicon carbide material has a rich pore structure, which can provide space for the shuttle and volume expansion of sulfur;
[0094] The pore size distribution of porous silicon carbide materials used as anode carriers for lithium-sulfur batteries was analyzed using a fully automatic mercury intrusion porosimeter. Fig.15 As shown, the total porosity of the porous carbon material reaches 65.2223%.
[0095] Application Example 2:
[0096] The special-shaped porous material prepared in any one of Examples 1 to 4 is applied to the anode support tube of a solid oxide fuel cell.
[0097] Application Example 3:
[0098] The special-shaped porous material prepared in Example 5 is applied in porous carbon material which is a thermal energy storage carrier material.
[0099] Application example 4:
[0100] The special-shaped porous material prepared in Example 6 is applied to the porous silicon carbide material as the anode carrier of the lithium-sulfur battery.
[0101] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0102] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a special-shaped porous material by additive manufacturing technology, characterized in that: The following steps are involved: Step 1: Mix and dissolve polyethersulfone, polyvinylpyrrolidone and N,N-dimethylpyrrolidone to obtain a phase conversion solution; Step 2: Evenly mix the phase conversion solution and the powder material to obtain a viscous slurry; Step 3: Set the 3D printing model as needed, inject the viscous slurry into the direct writing 3D printer, adjust the printing parameters, print the model, and obtain a sample green body with a three-level macroporous structure; Step 4: transferring the green sample into deionized water for curing; Step 5: vacuum dry the solidified sample and then sinter it to obtain a special-shaped porous material.
2. The method for preparing a special-shaped porous material by additive manufacturing technology according to claim 1, characterized in that: In the step 1, the mass ratio of polyethersulfone, polyvinylpyrrolidone and N,N-dimethylpyrrolidone is 2-5:1:7-20.
3. The method for preparing a special-shaped porous material by additive manufacturing technology according to claim 1, characterized in that: In the step 2, the mass ratio of the powder material to the phase conversion solution is 5-15:2-13; the phase conversion solution and the powder material are mixed uniformly by grinding and mixing.
4. The method for preparing a special-shaped porous material by additive manufacturing technology according to claim 1, characterized in that: In the step 2, the powder material is a mixed powder material obtained by ball milling NiO, 8YSZ and graphite for 12 to 36 hours; wherein NiO and 8YSZ are mixed in a mass ratio of 65wt%:35wt%, and then 5 to 12.5wt% of graphite is added; and in the step 5, the sintering process is: the sample is heated to 1000 to 1100°C at a heating rate of 1 to 3°C / min in an air atmosphere in a tubular furnace and kept warm for 3 to 6 hours, then heated to 1350 to 1450°C at a heating rate of 1 to 3°C / min and kept warm for 3 to 6 hours, the temperature in the furnace is naturally reduced, and then placed in a tubular furnace and heated to 750 to 850°C at a heating rate of 1 to 3°C / min in a hydrogen atmosphere, and kept warm for 1 to 3 hours.
5. The method for preparing a special-shaped porous material by additive manufacturing technology according to claim 1, characterized in that: In the step 2, the powder material is a mixture of single-layer graphene oxide and carboxylated multi-walled carbon nanotubes; and in the step 5, the sintering process is: heating the sample to 950-1100° C. in an Ar gas atmosphere using a tubular heating furnace, keeping the temperature for a period of time, and then cooling.
6. The method for preparing a special-shaped porous material by additive manufacturing technology according to claim 1, characterized in that: In the step 2, the powder material is SiC; and in the step 5, the sintering process is: heating the sample to 950-1100° C. in an Ar gas atmosphere using a tubular heating furnace, keeping the temperature for a period of time, and then cooling.
7. The method for preparing a special-shaped porous material by additive manufacturing technology according to claim 1, characterized in that: In the step three, the printing parameters are: extruding the slurry at a pressure of 0.1-0.6 MPa, a moving speed of 0.5-5 mm / s, and a nozzle diameter of 0.2-1 mm; in the step four, the curing time is 6-18 hours; in the step five, the vacuum drying temperature is 80-100°C.
8. Use of the irregular porous material prepared by the preparation method as claimed in claim 4 in anode support tubes of solid oxide fuel cells.
9. Use of the irregular porous material prepared by the preparation method as claimed in claim 5 in porous carbon materials as thermal energy storage carrier materials.
10. Use of the irregular porous material prepared by the preparation method as claimed in claim 6 in porous silicon carbide material as an anode carrier of a lithium-sulfur battery.